Study of Tensile Behaviour of Polymer Hybrid Composite at High Strain Rates - Arun Kumar Singh; Arunesh Kumar Srivastava (International Journal of Scientific Research in Mechanical and Materials Engineering, 2025)
The present study reports the strain rate dependence of tensile properties in p-Aramid, Ultra high Molecular Weight Polyethylene (UHMWPE) and p-Aramid/UHMWPE based compression moulded hybrid composites. A Split Hopkinson’s Pressure Bar (SHPB) apparatus capable of conducting tensile testing was used for experimental investigation at different strain rate varying from 1400/s to 2000/s. The effect of strain rate on failure behaviour of such composites has been experimentally evaluated. It is found that the stress to failure in these composites is enhanced with increase of strain rate. There is a radical change in magnitude of peak stress of p-Aramid composites by 32% with the variation of strain rate from 1400/s to 2000/s as compared to 8% and 17% peak stress variation for UHMWPE and p-Aramid/UHMWPE hybrid composites, respectively. A viscoelastic material model to describe the strain rate dependent tensile behaviour of hybrid composite is also presented, where the rate dependent characteristics of the hybrid composite has been described by three term Maxwell model. The result of material model has been compared with the experimental results. It is observed to have a good match between the predicted (mathematical model) and experimental results with only variation of 4% to 9%.